Handbook of developmental neurotoxicology - Slikker, William, Jr; Paule, Merle G.; Wang, Cheng, 1954- (Academic Press, an imprint of Elsevier, 2018)
Handbook of Developmental Neurotoxicology, Second Edition, provides a comprehensive view of the fundamental aspects of neurodevelopment, the pathways and agents that affect them, relevant clinical syndromes, and risk assessment procedures for developmental neurotoxicants. The editors and chapter authors are internationally recognized experts whose collaboration heralds a remarkable advance in the field, bridging developmental neuroscience with the principles of neurotoxicology. The book features eight new chapters with newly recruited authors, making it an essential text for students and professionals in toxicology, neurotoxicology, developmental biology, pharmacology, and neuroscience.